Fungal Keratitis Caused by Drechslera spp. Treated with Voriconazole: A Case Report - Margarita I. Echavez; Archimedes Lee D. Agahan; Noel S. Carino (Case Reports in Ophthalmological Medicine)
Objective. To present a case of Drechslera spp. keratitis treated with topical Voriconazole. Method. A case report. Results. A 52-year-old diabetic male presented with a one-week history of foreign body sensation of the left eye, self-medicated with Neomycin, Polymyxin B, and Dexamethasone eye drops, and was diagnosed to have bacterial conjunctivitis, which was treated with Levofloxacin drops. The patient developed a corneal opacity after 2 days and was initially seen with a visual acuity of counting fingers on the left eye, with a 3 mm central corneal ulcer with feathery borders. No hypopyon was noted. The right eye had a visual acuity of 20/20 and had unremarkable findings. Corneal scraping of the ulcer showed no organisms on Gram and Giemsa stain. Cultures were positive for Drechslera spp. and patient was started on Natamycin drops every 15 minutes, Atropine drops 3× a day, and Levofloxacin was continued every 4 hours. The ulcer increased to 4 mm, the infiltrates became deeper involving the midstroma, and there was appearance of a 2 mm hypopyon. Natamycin was shifted to Voriconazole eye drops every 15 minutes. There was note of a decrease in the size of the ulcer and clearing of the infiltrates with the new treatment regimen. Final visual acuity after 29 days of treatment was 20/40 with note of a slight corneal haze in the area of the previous ulcer. Conclusion. Voriconazole may be safe and effective in the treatment of Drechslera keratitis. There was no perforation and there was immediate decrease in the size of the ulcer. This is the first known case of Drechslera keratitis treated with Voriconazole eye drops in the Philippines.